Pro-osteogenesis and in vivo tracking investigation of a dental implantation system comprising novel mTi implant and HYH-Fe particles - Xiyu Li; Juan Wu; Danxue Li; Qin Zou; Yi Man; Ling Zou; Wei Li (Bioactive Materials, 2021)
Insufficient early osteogenesis seriously affects the later stage osteogenic quality and osseointegration of dental implants. To promote early osteogenesis, we first designed a Ti dental implant with a built-in magnet (mTi) to produce a local static magnetic field (SMF). Then, a dental implantation system comprising the mTi implant and the superparamagnetic hydroxyapatite (HA:Yb/Ho–Fe, named HYH-Fe) particles was implanted into the alveolar bone of beagles. The results showed that the mTi + HYH-Fe group displayed better early osteogenesis and later stage osseointegration than the Ti + HA and mTi + HA groups. A combination of the local SMF (mTi) and superparamagnetic HYH-Fe particles had a positive effect on the pro-osteogenesis of Ti implants. The results also indicated that week 10 could be adopted as the key time point to evaluate the early osteogenic effect of the mTi + HYH-Fe implantation system, which would be a promising prospect for promotion of osteogenesis, in vivo tracking investigation of material-bone relationships, and clinical applications.